Birds and Roads: Reduced Transit for Smaller Species over Roads within an Urban Environment - Johnson, Christopher D.; Evans, Daryl; Jones, Darryl (Frontiers in Ecology and Evolution, 2017)
Roads provide humans with a means of mobility between destinations, be it for transportation of goods and services or as a means of connecting with others. However, roads are also known to contribute towards a number of deleterious landscape processes, such as habitat destruction and fragmentation, pollution (e.g. chemical, noise and light) and animal mortality. Few studies however have investigated their effects on avifauna. We investigated the influence of road width on movements of nearby bird assemblages in Australia by comparing crossing counts of four species guilds and sizes over roads of varying widths in Southern Brisbane. In addition, we also sought to determine the association of seasonality with species crossing richness and abundance. Species guild affiliations were based on definitions from previous literature: small forest dependent, large forest dependent, honeyeater and urban tolerant; whereas body size classifications were arbitrarily defined: small (<20cm), medium (20-29cm) and large (>30cm). Road sites were selected based on their vegetation likeness, both within and between sites, and this was assessed using the Specht classification system. We detected strong, negative correlations between road width and forest species richness, crossing species richness and species crossing abundance. In particular, analysis of species guild classifications revealed species richness and crossing likelihoods of the small forest dependent guild to be consistently lower than those of large forest dependent, honeyeater and urban tolerant guilds. Analysis of species by body size classification yielded similar outcomes: small birds were consistently less likely to be present nearby and cross over roads of all widths compared to medium and large birds. We believe gap permeability, particularly changes in vegetation structure and complexity that may restrict a species ability to access to the gap, as well as competition and predation, play an important role in determining species presence and crossing likelihood. Dense vegetation is known to benefit smaller species due to the provision of foraging resources and shelter from larger, more aggressive species.